Impact of covid-19 on people living with HIV-1: care and prevention indicators at a local and nationwide level, Santo André, Brazil - Matsuda, Elaine Monteiro; Oliveira, Isabela Penteriche de; Bao, Laura Ballesteros; Manzoni, Fernanda Matsuda; Campos, Norberto Camilo; Varejão, Beatriz Brajal; Leal, Maristelly Pereira; Nascimento, Vania Barbosa; Brígido, Luís Fernando de Macedo (Revista de Saúde Pública, 2022)
The world has been dealing with Aids for forty years, covid-19 accentuated societal inequalities and promoted a rupture in care and prevention, including for people living with HIV. We compiled official HIV indicators, analyzed the impact of covid-19 in Brazil, at São Paulo State (SP), and compared it to the municipality of Santo André (in the state of São Paulo), which adopted linkage/retention strategies to mitigate the impact of covid-19. From 2019 to 2020, suppression/adhesion rates remained stable. The number of new treatments decreased both in Brazil (-19.75%) and São Paulo (-16.44%), but not in Santo André, where 80% of new patients started treatment within 30 days from their first TCD4 test (70% in São Paulo and 64% in Brazil). However, PrEP dispensing increased during this period. The distribution of 2,820 HIV self-tests in Santo André lead to only one documented new HIV diagnosis linked to care. Synergistic strategies to swiftly diagnose and connect new cases, ensuring retention as well as rescuing missing patients deserve priority in the fight against HIV, especially in times of covid-19.